Health Literacy and Shared Decision-making: Exploring the Relationship to Enable Meaningful Patient Engagement in Healthcare - Muscat, Danielle M.; Shepherd, Heather L.; Nutbeam, Don; Trevena, Lyndal; McCaffery, Kirsten J. (Journal of general internal medicine : JGIM, 2021)
Research into health literacy and shared decision-making has largely developed along parallel, but distinct lines over the past two decades. There is little evidence that the concepts and related practice have intersected except in the most functional way, for example, to simplify shared decision-making tools by improving readability scores of decision aids. This paper presents an integrated model to strengthen and sustain patient engagement in health care by drawing on the strengths of both concepts. This includes addressing patients’ skills and capacities, alongside modifications to written and verbal information. We propose an expanded model of shared decision-making which incorporates health literacy concepts and promotes two-tiered intervention methods to improve the targeting and personalization of communication and support the development of transferable health literacy skills among patients.